2021
DOI: 10.1021/acs.macromol.0c01756
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pH on the Growth and the Local Dynamics of Polyelectrolyte Multilayers

Abstract: Polyelectrolyte multilayers (PEMs) have been prepared using the strong polycation poly­(diallyldimethylammonium chloride) and the weak polyanion poly­(ethylene-alt-maleic acid) [P­(E-alt-MA)]. The spin label (SL) 4-amino-2,2,6,6-tetramethylpiperidine 1-oxide was covalently attached to the polyanion [SL-P­(E-alt-MA)] to monitor changes in the signal intensity as a measure of the layer growth and the line shape of the spectra indicative of the polymer chain mobility obtained by continuous wave electron paramagne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 32 publications
3
16
1
Order By: Relevance
“…A reason could be the nonelectrostatic interactions as possibly additional hydrogen bonds at pH 3, leading to more inter- and intramolecular interactions between the polymers, and thus, to lower mobility of SL-P­(E- alt -MA) within the PEMs. At pH 5 and 6, there should be no significant loss of radical concentration visible, as stated in our earlier study . Indeed, the calculated loss of 8% (pH 5) and 6% (pH 6) are within the uncertainty of the plotted values I Int .…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…A reason could be the nonelectrostatic interactions as possibly additional hydrogen bonds at pH 3, leading to more inter- and intramolecular interactions between the polymers, and thus, to lower mobility of SL-P­(E- alt -MA) within the PEMs. At pH 5 and 6, there should be no significant loss of radical concentration visible, as stated in our earlier study . Indeed, the calculated loss of 8% (pH 5) and 6% (pH 6) are within the uncertainty of the plotted values I Int .…”
Section: Resultssupporting
confidence: 84%
“…These values have been calculated by the averaged differences (1 d/6 d) of N = 22–30 (last 5 values). This loss of radical concentration at low pH was already described in the literature . At low pH, the radical is not stable.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…However, they neglect the implication of the emergence of heterogeneous structures in the emergence of non-linear growth on polyelectrolyte multilayers. Very recently, Naas et al [129] has shown using electron paramagnetic resonance spectroscopy that the appearance of different types of growth in polyelectrolyte multilayers results from a combination of different aggregation patterns of polyelectrolyte multilayers upon the deposition and modifications on the adsorption dynamics.…”
Section: Number Of Bilayers Nmentioning
confidence: 99%